Public Perception About Vaccination Service Information Through Instagram Account - Ayu Diah Oktaviana; Kukuh Sinduwiatmo (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine and describe the public perceptionof followers of the Instagram account @upt_puskesmas_sukodono about vaccination services at the Sukodono Public Health Center. The study uses a qualitative method with a descriptive approach. Data collection was carried out through in-depth interview, observation and documentation using informant determination technique by purposive sampling. The data analysis technique used is descriptive with the source of data coming from interview with the stages of data collection, reduction, data assessment and drawing conclusions. The results of this study indicate that the informants feel that the uploads on the @upt_puskesmas_sukodono account are informative. Therefore, these perception indicators are very important in influencing the informants, so that the informants can give their perception of vaccination service information through the @upt_puskesmas_sukodono Instagram account. In addition, the informants chose the @upt_puskesmas_sukodono account as their account in seeking information about vaccination services because this account always provides accurate and reliable information. It indirectly changes people’s mindset about their need to get the information they need quickly and practically.